Peculiarities in construction of segmentation models: theory and practice - Viselgaitė, Daiva; Vilys, Mantas (Business, Management and Economics Engineering, 2011)
Strategic marketing development is a major area of Lithuanian manufacturing companies, which seeks to improve business. In order to develop a strategic marketing plan, companies encompassing several business models are faced with the need to adapt those models here and highlight the lack of skills to carry out marketing activities for the sharp divide in the business models in the marketing literature. In order to give the latter companies a theoretical foundation for development of strategic marketing for sustainable business, which highlights the need for business model adaptation in the process of segmentation, it is worthwhile to analyze the scientific segmentation models and prepare recommendations for model construction. The scientific article is based on marketing research in window manufacturing and mounting business that enables to create a step-by-step market segmentation model, which is based on adaptation of different business models. The main tendencies identified in the sector (high market and technological uncertainty, intense competition) makes it a very characteristic example of a business, which seeks to improve competitiveness.